Spirituality, healing and medicine. - Aldridge, D (1991)
The natural science base of modern medicine influences the way in which medicine is delivered and may ignore the spiritual factors associated with illness. The history of spirituality in healing presented here reflects the growth of scientific knowledge, demands for religious renewal, and the shift in the understanding of the concept of health within a broader cultural context. General practitioners have been willing to entertain the idea of spiritual healing and include it in their daily practice, or referral network. Recognizing patients' beliefs in the face of suffering is an important factor in health care practice.